Precise Point Set Registration Based on Feature Fusion. (11th August 2021) - Liu, Yuying; Du, Shaoyi; Cui, Wenting; Wang, Xijing; Mou, Qingnan; Zhao, Jiamin; Guo, Yucheng; Zhang, Yong
Abstract: This paper proposed a novel precise point set registration method based on feature fusion for three-dimensional data. Firstly, for the prominent foreground with dense and continuous cluster structure, we propose an automatic extraction method combining the principal component analysis projection and density-based clustering method. Secondly, for point sets containing noises, we introduce correntropy measurement into registration to weaken their influence. Thirdly, for the precise registration of uneven distribution of points in the same point set, we propose a feature fusion based algorithm which is distribution specific, using point-to-point measurement for densely distributed foreground and point-to-plane measurement for sparsely distributed background, in case that only one measurement method is used for the whole point set the registration gets trapped into local extremum. Finally, we give the optimization algorithm of the proposed method. We conduct experiments on real orthodontics scenes to verify the effectiveness of our proposed feature extraction method and registration algorithm, and experimental results demonstrate that both the proposed solutions are proper for their respective tasks than other existing methods.